The Compassionate Global Brand: A Bridge Between Brand Globalness and Brand Love for Sustainable Brands - Nareswari, Ayu (Jurnal Ilmu Manajemen Advantage, 2023)
Finding out and assessing how global brand compassion affects global brand love and globalness in the direction of sustainable brand is the aim of this study. The primary source of data for this study was the answers that participants gave to the questionnaire items. All MSMEs in Jember Regency that export goods make up the population used. Thus, the study's sample consists of up to 100 MSMEs exporting goods from Jember Regency. The Structural Equation Model (SEM) with SmartPLS is the analytical tool utilized in this work. The findings demonstrated that Sustainable Brand benefits from Brand Globalness. The findings demonstrated that investors in Global Brand Compassion are positively impacted by Brand Globalness. The findings demonstrated that Sustainable Brand is positively impacted by Brand Love. The findings demonstrated that Global Brand Compassion investors benefit from Brand Love. The findings demonstrated the beneficial relationship between Global Brand Compassion and Sustainable Brand. The findings demonstrated that Global Brand Compassion, a component of Global Brand Globalness, positively influences Sustainable Brand. The findings demonstrated that Global Brand Compassion, through Brand Love, has a good impact on Sustainable Brand.